Implementation of Guided Discovery Learning Model with SETS Approach Assisted by Chemistry E-Module to Improve Creative Thinking Skills of Students - Yerimadesi Yerimadesi; Yulia Asri Warlinda; Hardeli Hardeli; Andromeda Andromeda (Postgraduate, University of Mataram, 2022)
Creative thinking skills can train and develop thinking processes in finding new ideas and ideas to solve chemical problems and problems through discovery, exploration, experimentation, showing and demonstrating similarities, differences, and consistency. Therefore, it is necessary to update what has been learned, such as choosing the right strategy. This study aims to demonstrate the effect of implementing a guided discovery learning model using a SETS approach supported by the chemical Young's modulus on the creative thinking skills of students in the SMAN 1 Padang XI class. The method used was a quasi-experimental study with a randomized control group posttest-only design. The population of this study is all SMAN 1 Padang Class XI students enrolled in the 2021/2022 academic year, which includes 7 classes. A study population is grouped using random sampling techniques. The non-testing tools used were the Student Profile Assessment Form and the Creativity Assessment Criteria. The data analysis technique in this study was quantitative data analysis, testing hypotheses by using two unpaired samples in the mean similarity test analysis tcount> ttable.Â The result of the hypothesis test indicates that the research hypothesis is accepted. This means that the implementation of the Guided Discovery Learning Model using the SETS approach supported by the Electrochemistry module has had a significant impact on the creative thinking skills of students in Class XI at SMA 1 Negeri Padang